AFM negatively regulates the infiltration of monocytes to mediate sepsis-associated acute kidney injury - Guo, Caiyun; Fan, Youling; Cheng, Jiurong; Deng, Yingdong; Zhang, Xiangsheng; Chen, Yanna; Jing, Huan; Li, Wenjun; Liu, Pei; Xie, Jiaqi; Ning, Wenjun; Chen, Hongtao; et al. (Frontiers in Immunology, 2023)
Abstract Background: Sepsis is organ dysfunction due to the host’s deleterious response to infection, and the kidneys are one of the organs damaged in common sepsis. Sepsis-associated acute kidney injury (SA-AKI) increases the mortality in patients with sepsis. Although a substantial volume of research has improved the prevention and treatment of the disease, SA-SKI is still a significant clinical concern. Purpose: Aimed to use weighted gene co-expression network analysis (WGCNA) and immunoinfiltration analysis to study SA-AKI-related diagnostic markers and potential therapeutic targets. Methods: Immunoinfiltration analysis was performed on SA-AKI expression datasets from the Gene Expression Synthesis (GEO) database. A weighted gene co-expression network analysis (WGCNA) analysis was performed on immune invasion scores as trait data, and modules associated with immune cells of interest were identified as hub modules. Screening hub geneset in the hub module using protein-protein interaction (PPI) network analysis. The hub gene was identified as a target by intersecting with significantly different genes screened by differential expression analysis and validated using two external datasets. Finally, the correlation between the target gene, SA-AKI, and immune cells was verified experimentally. Results: Green modules associated with monocytes were identified using WGCNA and immune infiltration analysis. Differential expression analysis and PPI network analysis identified two hub genes (AFM and GSTA1). Further validation using additional AKI datasets GSE30718 and GSE44925 showed that AFM was significantly downregulated in AKI samples and correlated with the development of AKI. The correlation analysis of hub genes and immune cells showed that AFM was significantly associated with monocyte infiltration and hence, selected as a critical gene. In addition, Gene single-enrichment analysis (GSEA) and PPI analyses results showed that AFM was significantly related to the occurrence and development of SA-AKI. Conclusions: AFM is inversely correlated with the recruitment of monocytes and the release of various inflammatory factors in the kidneys of AKI. AFM can be a potential biomarker and therapeutic target for monocyte infiltration in sepsis-related AKI.